(3HdZI GdXQaGA Edi eYQaI JhGQjN GdNdaGAs - (3CHh GdMSf Ydj Hf CHj YHO Gddg eMeO Hf CHj GdSQhQ Hf YHO GdQMef GdQhNjs
(3ChdgG (B:s
(3bGd GdTjN GdEeGe Gdabjg CHh GdMSf Ydi CeG HYO , aEfi PGcQ ai cJGHi gPG fSH QShd Gddg Udi Gddg Ydjg hSde hBdg hSde hfPcQ GdVjGA fSH ef hdi HYOg ef GdNdaGA GdeTghQjf s
(3BNQgG (B:s
(3hcGfJ haGI Gdedc GdCTQa HOeTb jhe GdNejS QGHY GdeMQe SfI NeS hKdGKjf hSJeGjg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJGQjNs